How does the regular work of WTO influence regional trade agreements? - Devin McDaniels; Ana Cristina Molina; Erik Wijkström (World Trade Organization (WTO), 2018)
This paper illustrates how the work of the WTO's standing committees is fuelling regulatory cooperation between WTO members, and inspiring RTA negotiators. We explore, as a case study, how the WTO TBT Committee has shaped provisions on international standards in RTAs, and focus on the extent to which RTAs have assimilated the WTO TBT principles for development of international standards (the Six Principles), arguably the most important decision taken by the TBT Committee over last 20-plus years. Our analysis covers 260 RTAs, and shows that while most RTAs are silent on the matter, one quarter have provisions where the Parties commit to implement WTO TBT principles, and, among these, a few go further still - for example by naming specific international standardizing bodies which are relevant in certain sectors. In addition, the RTAs sharpen and harden the Six Principles by making them directly applicable to the parties.
Keywords: F13; F15; F53; F55; K33; L15; 330; regional Trade Agreements; international standards; international cooperation; coherence; non-tariff barriers; technical barriers to trade; regulation